Hydrogen evolution electrode material with high catalytic activity as well as preparation method and application of hydrogen evolution electrode material
By preparing tungsten-iron-chromium co-doped cobalt phosphide nanomaterials on nickel foam, the problems of poor conductivity and easy aggregation of active sites of cobalt phosphide were solved, and efficient and stable hydrogen production performance by water electrolysis was achieved.
Patent Information
- Application Number
- CN202511696777.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-02-03
AI Technical Summary
In existing technologies, cobalt phosphide, a single component, has poor intrinsic conductivity and its active sites are prone to aggregation, which limits its catalytic efficiency. Furthermore, platinum-based precious metal materials are expensive and difficult to widely apply to hydrogen production via water electrolysis.
A tungsten-iron-chromium co-doped cobalt fluoride/nickel foam precursor was prepared on nickel foam by a hydrothermal method. Combined with low-temperature phosphating treatment, a tungsten-iron-chromium co-doped cobalt phosphide nanomaterial was constructed to form a three-dimensional porous nanorod array structure, thereby optimizing the electronic structure and distribution of active sites.
It significantly improves the catalytic activity and stability of the hydrogen evolution electrode, increases the specific surface area and the number of active sites, reduces the adhesion between the electrode and bubbles, and improves the operational stability under reaction kinetics and current density.
Smart Images

Figure CN121451229A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen evolution electrode technology, and in particular to a highly catalytically active tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material, its preparation method, and its application. Background Technology
[0002] Hydrogen energy, as a clean and efficient secondary energy source, is a core clean energy source for achieving the goal of "carbon neutrality." Electrolysis of water to produce hydrogen is one of the most promising green hydrogen production technologies. The core challenge for its large-scale application lies in developing efficient, stable, and low-cost electrocatalysts for the hydrogen evolution reaction. Currently, the best-performing hydrogen evolution catalysts are still platinum-based precious metal materials, but their high cost and scarcity severely restrict their widespread application.
[0003] Transition metal phosphides, particularly cobalt phosphide, are considered promising alternatives to platinum due to their platinum-like electronic structure and excellent hydrogen evolution catalytic activity. However, single-component cobalt phosphide exhibits poor intrinsic conductivity and its active sites tend to aggregate, limiting its catalytic efficiency.
[0004] Nickel foam, as a three-dimensional porous conductive substrate, is widely used to load active materials to construct self-supporting electrodes, avoiding the problems of decreased conductivity and blockage of active sites caused by polymer binders. However, how to significantly improve the hydrogen evolution performance of nickel foam by growing nanomaterials with multi-element synergistic effects, abundant active sites, and stable structures remains a challenge in this field. Summary of the Invention
[0005] The purpose of this invention is to address the technical deficiencies in the prior art by providing a hydrogen evolution electrode material with high catalytic activity, its preparation method, and its application.
[0006] The technical solution adopted to achieve the purpose of this invention is: A method for preparing a hydrogen evolution electrode material with high catalytic activity includes the following steps: Step 1: Clean the nickel foam to remove organic contaminants and oxides from the surface; Step 2: Prepare the tungsten-iron-chromium co-doped cobalt hydroxyl fluoride / nickel foam precursor WFeCrCo(OH)F / NF on nickel foam using a hydrothermal method: Cobalt nitrate hexahydrate Co(NO3)2·6H2O, sodium tungstate dihydrate Na2WO4·2H2O, ferric nitrate nonahydrate Fe(NO3)3·9H2O, chromium nitrate nonahydrate Cr(NO3)3·9H2O, urea, and ammonium fluoride NH4F were dissolved in deionized water to form a homogeneous hydrothermal reaction solution. Cleaned nickel foam was immersed in the reaction solution and transferred to a reaction vessel. The reaction vessel was placed in an oven for hydrothermal reaction. The obtained precursor was washed several times with ethanol and deionized water and dried to obtain WFeCrCo(OH)F / NF. Step 3: Place the WFeCrCo(OH)F / NF and sodium hypophosphite powder obtained in Step 2 at two different positions on a ceramic boat, with the sodium hypophosphite powder located on the upstream side of the tube furnace. Keep the boat warm in a protective gas environment and then allow it to cool naturally to room temperature to obtain the tungsten-iron-chromium co-doped cobalt phosphide composite electrode material WFeCr-CoP / NF.
[0007] In the above technical solution, step 1, the step of cleaning the foamed nickel is as follows: the foamed nickel is placed in acetone, hydrochloric acid and deionized water for ultrasonic cleaning in sequence.
[0008] In the above technical solution, in step 2, the hydrothermal reaction solution contains 1.8~2.0 mmol of Co(NO3)2·6H2O, 0.3~0.8 mmol of Na2WO4·2H2O, 0.1~0.5 mmol of Fe(NO3)3·9H2O, 0.2~0.5 mmol of Cr(NO3)3·9H2O, 5~15 mmol of urea, and 2~6 mmol of ammonium fluoride NH4F.
[0009] In the above technical solution, in step 2, the temperature of the hydrothermal reaction is 100~150 ℃, and the time of the hydrothermal reaction is 4~10 h.
[0010] In the above technical solution, the drying temperature in step 2 is 50~70 ℃.
[0011] In the above technical solution, in step 3, the sodium hypophosphite powder is 15 to 20 times the mass of WFeCrCo(OH)F / NF.
[0012] In the above technical solution, in step 3, the protective gas is argon, the holding temperature is 200~400 ℃, the holding time is 2~4 h, and the heating rate is 1~2 °C min. -1 .
[0013] Another aspect of the present invention includes a tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material obtained by the preparation method described above.
[0014] In the above technical solution, the molar ratio of tungsten to cobalt in the tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material is (0.3-0.8):2, preferably (0.5-0.8):2, and more preferably 0.8:2.
[0015] Another aspect of the present invention includes the application of the aforementioned tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material in water electrolysis for hydrogen production.
[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The highly catalytically active nickel-based hydrogen evolution electrode material disclosed in this invention is prepared by combining hydrothermal and low-temperature phosphating methods. Through the synergistic doping of tungsten, iron, and chromium, the electronic structure of cobalt phosphide is effectively regulated, optimizing its adsorption behavior for reaction intermediates and significantly improving the intrinsic catalytic activity of the material. Fe can regulate the electronic structure of the catalyst, optimize the hydrogen adsorption free energy, and promote water decomposition. Cr can promote water adsorption and diffusion, and Cr has high oxyphilicity, which can greatly inhibit the oxidation of transition metal phosphides, giving the catalyst excellent stability. On the one hand, the synergistic effect of Fe, Cr, and W can regulate the ease of hydrogen adsorption and desorption, thereby reducing the reaction energy barrier; on the other hand, since W has a larger atomic radius than Fe and Cr, the incorporation of W can change the crystal structure of the catalyst and increase defects, further improving the catalytic activity.
[0017] 2. By fixing the doping amounts of Fe and Cr and adjusting the concentration of W separately, the effect of W doping amount on material performance was evaluated. The results showed that the catalytic performance of the electrode material was significantly improved, indicating that W plays a key role in regulating the electronic structure of CoP and optimizing hydrogen adsorption behavior.
[0018] 3. The three-dimensional porous nanorod array structure constructed in situ on nickel foam in this invention not only significantly increases the specific surface area and the number of active sites, but also reduces the adhesion force between the electrode and the bubble, which is beneficial to mass transport and thus enhances the reaction kinetics and operational stability under high current density. Attached Figure Description
[0019] Figure 1 The X-ray diffraction (XRD) curves of WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3 are shown. Figure 2The images show SEM images of the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Specifically, a is the SEM image of the undoped CoP / NF electrode material prepared in Comparative Example 1, b is the SEM image of the WFeCr-CoP-0.3 / NF hydrogen evolution electrode material prepared in Example 1, c is the SEM image of the WFeCr-CoP-0.5 / NF hydrogen evolution electrode material prepared in Example 2, and d is the SEM image of the WFeCr-CoP-0.8 / NF hydrogen evolution electrode material prepared in Example 3. Figure 3 The images show TEM images of the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Specifically, a is a TEM image of the undoped CoP / NF electrode material prepared in Comparative Example 1, b is a TEM image of the WFeCr-CoP-0.3 / NF hydrogen evolution electrode material prepared in Example 1, c is a TEM image of the WFeCr-CoP-0.5 / NF hydrogen evolution electrode material prepared in Example 2, and d is a TEM image of the WFeCr-CoP-0.8 / NF hydrogen evolution electrode material prepared in Example 3. Figure 4 Electrochemical impedance spectroscopy of the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Figure 5 The linear scan curves of electrocatalytic hydrogen evolution are shown for the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Figure 6 Tafel curves are shown for the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Figure 7 The double-layer capacitance diagrams are shown for the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Detailed Implementation
[0020] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0021] Example 1 A tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material is prepared by the following steps: Step 1, Cleaning the nickel foam: First, pre-treat the nickel foam with acetone and 3M hydrochloric acid aqueous solution by ultrasonication for 10 min in sequence, and then treat it with deionized water by ultrasonication for 30 min. Step 2: Prepare the tungsten-iron-chromium co-doped cobalt hydroxyl fluoride / nickel foam precursor WFeCrCo(OH)F / NF on nickel foam using a hydrothermal method: 2.0 mmol of Co(NO3)2·6H2O, 0.3 mmol of Na2WO4·2H2O, 0.2 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Cr(NO3)3·9H2O, 10 mmol of urea, and 5 mmol of NH4F were added to 30 mL of deionized water and mixed thoroughly. The cleaned nickel foam was immersed in the reaction solution and transferred to a polytetrafluoroethylene-lined reactor. The reactor was placed in an oven and kept at 120 °C for 10 h. Finally, the obtained WFeCrCo(OH)F / NF was washed several times with ethanol and deionized water, and dried at 60 °C. Step 3: Anneal WFeCrCo(OH)F / NF to obtain WFeCr-CoP / NF hydrogen evolution electrode material: The prepared WFeCrCo(OH)F / NF and sodium hypophosphite powder (20 times the mass of WFeCrCo(OH)F / NF) were placed at two different locations on a ceramic boat, with the sodium hypophosphite powder located on the upstream side of the tube furnace. The furnace was then heated at 350 °C for 2 h under argon atmosphere, with a heating rate of 2 °C / min. -1 The hydrogen evolution electrode material, co-doped cobalt phosphide / nickel foam (WFeCr-CoP-0.3 / NF), can be obtained by naturally cooling it to room temperature.
[0022] Example 2 A tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material is prepared by the following steps: Step 1, Clean the nickel foam: First, the nickel foam was ultrasonically pretreated with acetone and 3M hydrochloric acid aqueous solution for 10 min in sequence, and then ultrasonically treated with deionized water for 30 min. Step 2: Prepare the tungsten-iron-chromium co-doped cobalt hydroxyl fluoride / nickel foam precursor WFeCrCo(OH)F / NF on nickel foam using a hydrothermal method: 2.0 mmol of Co(NO3)2·6H2O, 0.5 mmol of Na2WO4·2H2O, 0.2 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Cr(NO3)3·9H2O, 10 mmol of urea, and 5 mmol of NH4F were added to 30 mL of deionized water and mixed thoroughly. The cleaned nickel foam was immersed in the reaction solution and transferred to a polytetrafluoroethylene-lined reactor. The reactor was placed in an oven and kept at 120 °C for 10 h. Finally, the obtained WFeCrCo(OH)F / NF was washed several times with ethanol and deionized water, and dried at 60 °C. Step 3: Anneal WFeCrCo(OH)F / NF to obtain WFeCr-CoP / NF hydrogen evolution electrode material: The prepared WFeCrCo(OH)F / NF and sodium hypophosphite powder (20 times the mass of WFeCrCo(OH)F / NF) were placed at two different locations on a ceramic boat, with the sodium hypophosphite powder located on the upstream side of the tube furnace. The furnace was then heated at 350 °C for 2 h under argon atmosphere, with a heating rate of 2 °C / min. -1 The hydrogen evolution electrode material, co-doped cobalt phosphide / nickel foam (WFeCr-CoP-0.5 / NF), can be obtained by naturally cooling it to room temperature.
[0023] Example 3 A tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material is prepared by the following steps: Step 1, Clean the nickel foam: First, the nickel foam was ultrasonically pretreated with acetone and 3M hydrochloric acid aqueous solution for 10 min in sequence, and then ultrasonically treated with deionized water for 30 min. Step 2: Prepare the tungsten-iron-chromium co-doped cobalt hydroxyl fluoride / nickel foam precursor WFeCrCo(OH)F / NF on nickel foam using a hydrothermal method: 2.0 mmol of Co(NO3)2·6H2O, 0.8 mmol of Na2WO4·2H2O, 0.2 mmol of Fe(NO3)3·9H2O, 0.2 mmol of Cr(NO3)3·9H2O, 10 mmol of urea, and 5 mmol of NH4F were added to 30 mL of deionized water and mixed thoroughly. The cleaned nickel foam was immersed in the reaction solution and transferred to a polytetrafluoroethylene-lined reactor. The reactor was placed in an oven and kept at 120 °C for 10 h. Finally, the obtained WFeCrCo(OH)F / NF was washed several times with ethanol and deionized water, and dried at 60 °C. Step 3: Anneal WFeCrCo(OH)F / NF to obtain WFeCr-CoP / NF hydrogen evolution electrode material: The prepared WFeCrCo(OH)F / NF and sodium hypophosphite powder (20 times the mass of WFeCrCo(OH)F / NF) were placed at two different locations on a ceramic boat, with the sodium hypophosphite powder located on the upstream side of the tube furnace. The furnace was then heated at 350 °C for 2 h under argon atmosphere, with a heating rate of 2 °C / min. -1 The hydrogen evolution electrode material, co-doped cobalt phosphide / nickel foam (WFeCr-CoP-0.8 / NF), can be obtained by naturally cooling it to room temperature.
[0024] Comparative Example 1 A cobalt phosphide / nickel foam (CoP / NF) composite electrode material is prepared by the following steps: Step 1, Clean the nickel foam: First, the nickel foam was ultrasonically pretreated with acetone and 3M hydrochloric acid aqueous solution for 10 min in sequence, and then ultrasonically treated with deionized water for 30 min. Step 2: Prepare tungsten-iron-chromium co-doped cobalt hydroxyl fluoride / nickel foam precursor Co(OH)F / NF / NF on nickel foam using a hydrothermal method: 2.0 mmol of Co(NO3)2·6H2O, 10 mmol of urea, and 5 mmol of NH4F were added to 30 mL of deionized water and mixed thoroughly. The cleaned nickel foam was immersed in the reaction solution and transferred to a polytetrafluoroethylene-lined reactor. The reactor was placed in an oven and kept at 120 °C for 10 h. Finally, the obtained Co(OH)F / NF was washed several times with ethanol and deionized water, and dried at 60 °C. Step 3: Anneal the Co(OH)F / NF to obtain the CoP / NF composite electrode material: The prepared Co(OH)F / NF and sodium hypophosphite powder with a mass 20 times that of Co(OH)F / NF were placed at two different locations on a ceramic boat, with the sodium hypophosphite powder located on the upstream side of the tube furnace. The furnace was then heated at 350 °C for 2 h under argon atmosphere, with a heating rate of 2 °C / min. -1 The cobalt phosphide / nickel foam (CoP / NF) hydrogen evolution electrode material can be obtained by naturally cooling to room temperature.
[0025] Test Example 1 Figure 1The XRD curves of WFeCr-CoP / NF composite electrode materials with different doping concentrations in Examples 1-3 are shown. By comparing the diffraction peaks with those of standard CoP (JCPDS No. 29-0497), the successful preparation of hydrogen evolution electrode materials WFeCr-CoP-0.3 / NF, WFeCr-CoP-0.5 / NF, and WFeCr-CoP-0.8 / NF is demonstrated, indicating that the doping of tungsten, iron, and chromium does not change the basic crystal structure of the material.
[0026] Test Example 2 Figure 2 SEM images of the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF composite electrode materials with different doping concentrations prepared in Examples 1-3 are shown. Specifically, a is the SEM image of the undoped CoP / NF electrode material prepared in Comparative Example 1, b is the SEM image of the WFeCr-CoP-0.3 / NF hydrogen evolution electrode material prepared in Example 1, c is the SEM image of the tungsten-iron-chromium co-doped cobalt phosphide / nickel foam WFeCr-CoP-0.5 / NF hydrogen evolution electrode material prepared in Example 2, and d is the SEM image of the tungsten-iron-chromium co-doped cobalt phosphide / nickel foam WFeCr-CoP-0.8 / NF hydrogen evolution electrode material prepared in Example 3; through comparison... Figure 2 SEM images of different samples show that the undoped cobalt phosphide / nickel foam electrode material in sample a exhibits a well-arranged nanorod array morphology; while the hydrogen evolution electrode materials codoped with tungsten, iron, and chromium in samples b, c, and d still maintain a nanorod array morphology. This refined and dense nanostructure helps to increase the specific surface area to provide more active sites, laying the foundation for improving the electrocatalytic performance of the electrode.
[0027] Test Example 3 Figure 3 The images show TEM images of the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. Specifically, a is a TEM image of the undoped CoP / NF electrode material prepared in Comparative Example 1; b is a TEM image of the tungsten-iron-chromium co-doped cobalt phosphide / nickel foam WFeCr-CoP-0.3 / NF hydrogen evolution electrode material prepared in Example 1; c is a TEM image of the tungsten-iron-chromium co-doped cobalt phosphide / nickel foam WFeCr-CoP-0.5 / NF hydrogen evolution electrode material prepared in Example 2; and d is a TEM image of the tungsten-iron-chromium co-doped cobalt phosphide / nickel foam WFeCr-CoP-0.8 / NF hydrogen evolution electrode material prepared in Example 3. Figure 3 TEM images further confirm that the nanorods are well dispersed and that there are a large number of pores on the surface of the nanorods, which effectively increases the specific surface area, reduces the adhesion between the electrodes and the bubbles, and is beneficial for material transport.
[0028] Test Example 4 Figure 4 The electrochemical impedance spectroscopy (EIS) spectra of the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-4 are shown. The charge transfer resistance of WFeCr-CoP-0.5 / NF is only 0.9 Ω, which is much lower than that of WFeCr-CoP-0.8 / NF (2.1 Ω), WFeCr-CoP-0.3 / NF (5.4 Ω), CoP / NF (10.5 Ω), and NF (13.3 Ω), indicating that WFeCr-CoP-0.5 / NF has the fastest charge transfer kinetics, which is beneficial to improving electrochemical activity. Furthermore, compared with CoP / NF and NF, the results demonstrate that tungsten-iron-chromium co-doping can synergistically optimize the electronic structure of the material, significantly reduce charge transfer resistance, and accelerate the electrochemical reaction rate.
[0029] Test Example 5 Figure 5 Linear scanning curves of electrocatalytic hydrogen evolution for the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3 are shown. The NF substrate itself has extremely low catalytic activity, while the CoP / NF electrode exhibits significant catalytic activity, but its performance is limited. After introducing tungsten-iron-chromium multi-component doping, the catalytic performance of all hydrogen evolution electrodes is significantly improved. The catalytic activity shows a systematic increasing trend with increasing doping concentration, and the performance order is: WFeCr-CoP-0.8 / NF > WFeCr-CoP-0.5 / NF > WFeCr-CoP-0.3 / NF > CoP / NF > NF. Among them, WFeCr-CoP-0.8 / NF has the best catalytic activity.
[0030] Test Example 6 Figure 6 The Tafel curves are shown for the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. NF exhibits the largest Tafel slope (136.33 mV dec⁻¹), indicating its sluggish reaction kinetics and poorest catalytic activity. The slope of CoP / NF decreases to 118.66 mV dec⁻¹, showing some improvement in kinetics. After multi-component doping with tungsten, iron, and chromium, the Tafel slopes of all hydrogen evolution electrodes significantly decrease, and the slope shows a systematic decreasing trend with increasing doping concentration. Specifically, the values are: WFeCr-CoP-0.3 / NF (97.42 mV dec⁻¹). -1 )>WFeCr-CoP-0.5 / NF (86.11 mV dec-1 )>WFeCr-CoP-0.8 / NF (66.39 mV dec -1 Among them, WFeCr-CoP-0.8 / NF has the smallest Tafel slope, which proves that it has the fastest reaction kinetics and the best catalytic activity.
[0031] Test Example 7 Figure 7 The double-layer capacitance diagrams are shown for the undoped CoP / NF electrode material prepared in Comparative Example 1 and the WFeCr-CoP / NF hydrogen evolution electrode materials with different doping concentrations prepared in Examples 1-3. NF has the lowest double-layer capacitance (1.95 mF cm⁻¹). -2 This indicates that the number of active sites is limited. Meanwhile, the Cdl value of CoP / NF significantly increased to 16.05 mF cm⁻¹. -2 This demonstrates that CoP introduces more electrochemical active sites. After tungsten-iron-chromium multi-component doping, the Cdl values of all hydrogen evolution electrodes are higher than those of undoped CoP / NF, and the Cdl value shows a systematic increasing trend with increasing doping concentration, specifically: WFeCr-CoP-0.3 / NF (18.18 mF cm⁻¹). -2 ) <WFeCr-CoP-0.5 / NF (19.26 mF cm -2 ) <WFeCr-CoP-0.8 / NF(21.69 mF cm -2 Among them, WFeCr-CoP-0.8 / NF has the largest Cdl value, which can effectively increase the electrochemical active surface area of the material and expose more catalytic sites.
[0032] The above description is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a hydrogen evolution electrode material with high catalytic activity, characterized in that, Includes the following steps: Step 1: Clean the nickel foam to remove organic contaminants and oxides from the surface; Step 2: Prepare the tungsten-iron-chromium co-doped cobalt hydroxyl fluoride / nickel foam precursor WFeCrCo(OH)F / NF on nickel foam using a hydrothermal method: Cobalt nitrate hexahydrate Co(NO3)2·6H2O, sodium tungstate dihydrate Na2WO4·2H2O, ferric nitrate nonahydrate Fe(NO3)3·9H2O, chromium nitrate nonahydrate Cr(NO3)3·9H2O, urea, and ammonium fluoride NH4F were dissolved in deionized water to form a homogeneous hydrothermal reaction solution. Cleaned nickel foam was immersed in the reaction solution and transferred to a reaction vessel. The reaction vessel was placed in an oven for hydrothermal reaction. The obtained precursor was washed several times with ethanol and deionized water and dried to obtain WFeCrCo(OH)F / NF. Step 3: Place the WFeCrCo(OH)F / NF and sodium hypophosphite powder obtained in Step 2 at two different positions on a ceramic boat, with the sodium hypophosphite powder located on the upstream side of the tube furnace. Keep the boat warm in a protective gas environment and then allow it to cool naturally to room temperature to obtain the tungsten-iron-chromium co-doped cobalt phosphide composite electrode material WFeCr-CoP / NF.
2. The preparation method according to claim 1, characterized in that, In step 1, the step of cleaning the foamed nickel is as follows: the foamed nickel is placed in acetone, hydrochloric acid and deionized water in sequence for ultrasonic cleaning.
3. The preparation method according to claim 1, characterized in that, In step 2, the hydrothermal reaction solution contains 1.8–2.0 mmol of Co(NO3)2·6H2O, 0.3–0.8 mmol of Na2WO4·2H2O, 0.1–0.5 mmol of Fe(NO3)3·9H2O, 0.2–0.5 mmol of Cr(NO3)3·9H2O, 5–15 mmol of urea, and 2–6 mmol of ammonium fluoride (NH4F).
4. The preparation method according to claim 1, characterized in that, In step 2, the hydrothermal reaction temperature is 100~150 ℃, and the hydrothermal reaction time is 4~10 h.
5. The preparation method according to claim 1, characterized in that, In step 2, the drying temperature is 50~70 ℃.
6. The preparation method according to claim 1, characterized in that, In step 3, the sodium hypophosphite powder is 15 to 20 times the mass of WFeCrCo(OH)F / NF.
7. The preparation method according to claim 1, characterized in that, In step 3, the protective gas is argon, the holding temperature is 200~400 ℃, the holding time is 2~4 h, and the heating rate is 1~2 °C min. -1 .
8. A tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material obtained by any one of the preparation methods described in claims 1 to 7.
9. The tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material as described in claim 8, characterized in that, The molar ratio of tungsten to cobalt is (0.3-0.8):2, preferably (0.5-0.8):2, and more preferably 0.8:
2.
10. The application of the tungsten-iron-chromium co-doped cobalt-nickel phosphide-based hydrogen evolution electrode material as described in claim 9 in water electrolysis for hydrogen production.